(untitled) (Acta Scientiarum. Biological Sciences, 2013)
This study evaluated the influence of physical, chemical and physico-chemical variables of water on the biomass of periphyton community and verified the differences between six sampling sites over the course of São Mateus river: two upstream of the city of São Mateus, Espírito Santo State (E1, E2), two along (E3, E4), and two downstream of the city (E5, E6). The periphyton was collected from roots of Eichhornia crassipes (Mart.) Solms. Samplings were undertaken every week in September and October 2010. The periphyton biomass was estimated through chlorophyll ‘a’, biovolume, dry mass, ash-free dry mass, and ash. Higher values of chlorophyll ‘a’ were found at E1, while the total biovolume featured greater values in E4 and E3. Regarding the values of periphyton dry mass, the inorganic fraction was higher at sites along and downstream of the city of São Mateus. The variation of periphyton biomass was influenced by the availability of nutrients (phosphorus and nitrogen) and turbidity, as evidenced by the CCA. The results suggest that the input of allochthonous material, especially from human activities (fish farming and discharge of domestic and industrial wastewater), has changed the water quality (as pointed out by the PCA), as well as the communities present.